Polymorphism of Erythrocyte Potassium, Transferrin, Haemoglobin, Albumins and their Relationship with Several Milk Production Traits for Black and White Cattle in Turkey - Kemal Gurcan, E.; Ihsan Soysal, M. (Asian Journal of Chemistry, 2010)
Blood protein polymorphism such as erythrocyte potassium concentration (Ke), albumin (Al), transferrin (Tf) and haemoglobin (Hb) of Black and White cattle breed raised in Turkey were investigated in this study. The genetic constitution of herd with respect to these loci were examined. The relationship between blood protein types and several milk production traits were investigated. Several milk production traits such as milk yield, average daily milk yield and lactation length were compared with blood protein types. The haemoglobin and albumin loci were found as monomorphic. The only Hb-AA and Al-BB genotypes were observed. The KH and KL gene frequencies of erythrocytes potassium concentration loci were found as 0.92 and 0.08, respectively. Six different genotypes in transferrin loci were found as Tf-AA, Tf-DD, Tf-DE, Tf-AE, Tf-AD, Tf-EE and allele frequencies of Tf-A, Tf-D, Tf-E were 0.26, 0.58 and 0.16, respectively. Some significant differences were found among the transferrin genotypes with milk production traits. The averege daily milk yield of Tf-AA genotype was different from Tf- AD genotype (p < 0.01) and Tf-DD genotype was different from Tf-AD genotype (p < 0.05). Milk yield of Tf-AA genotype was significant higher than those of Tf-AE, TF-AD genotypes (p < 0.01). Differences between two erythrocyte potassium concentration genotypes were not significantly important for the traits of milk production (p > 0.05). The genetic structure of animal for four loci were determined. Significant relationship was not found between milk production traits and genotypes except transferrin genotype.